PENGARUH CARBON EMISSIONS DISCLOSURE TERHADAP EARNING QUALITY DENGAN KEPEMILIKAN INSTITUSIONAL SEBAGAI VARIABEL MODERASI (STUDI PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI TAHUN 2016-2018) - Rangga Sugmaprathama; Rahmiati Rahmiati (Balance: Media Informasi Akuntansi dan Keuangan, 2021)
The purpose of this study was to determine the effect of Carbon Emissions Disclosure on Earning Quality with Institutional Ownership as a moderating variable. Study of manufacturing companies listed on the IDX 2016-2018. This research uses quantitative research using purposive sampling as data analysis. This study uses secondary data in the form of time series, namely the company's annual report data on the IDX as well as the company's carbon emission disclosures on the company website which includes CED, EQ and KI, 2016-2018. The number of manufacturing companies sampled in this study were 18 companies with the criteria that they were listed on the IDX, as well as providing annual reports for the 2016-2018 period, and providing disclosure of carbon emissions. The data that has been obtained are then analyzed using the Eviews application tool version 11. The results of this study indicate that Carbon Emissions Disclosure affects Earnig Quality. Suggestions for further research are to add other variables and replace them with intervening variables or use other proxies. Also expected to be able to choose other independent variables such as funding decisions, capital structure, debt policy and others